Effects of silver diammine fluoride with/without potassium iodide on enamel and dentin carious lesions in primary teeth - Kaur, M.; Anderson, P.; Shahid, S.; Davis, G. R.; Mills, D.; Wong, F. S. L. (Frontiers in Oral Health, 2024)
AimTo assess the effects of SDF and SDF+KI treatment on enamel and dentin carious lesions in primary teeth using x-ray Microtomography (XMT) and back scattered scanning electron microscopy (BSE-SEM).MethodsArtificial enamel caries of 3 caries free primary teeth were created by immersion of the samples in 50 ml demineralization solution for 72 h. Three other teeth with natural dentin caries were selected. Both groups were divided into 3 subgroups: EC–Enamel Control; ES–Enamel with SDF application; ESK–Enamel with SDF followed by KI application; DC–Dentin Control; DS–Dentin with SDF application; DSK–Dentin with SDF followed by KI application. Each tooth was imaged using XMT at 3 time points: (1) Pretreatment; (2) after immersion in remineralization solution for 120 h, with or without SDF or SDF+KI; (3) after subsequent immersion in demineralization solution for 72 h. The change of radiopacities of the lesions in these time points were assessed from the XMT images. After the XMT scans, all teeth were investigated microscopically using BSE-SEM.ResultsIn EC, no change in linear attenuation coefficient (LAC) was observed after remineralization, but LAC reduction was observed after subsequent demineralization. For ES, thin layer of high LAC material was deposited on the enamel surface after remineralization, and further reduction of LAC was observed after demineralization. In ESK, the surface layer was lost after SDF+KI, and small reduction of LAC was observed after demineralization. In DC, no LAC change was observed after remineralization, but reduction of LAC was detected after demineralization. In DS, high LAC material was formed on the carious dentin surface and randomly inside the lesion. No further LAC change was found after demineralization. In DSK, thick layer of high LAC material was deposited on the carious surface and inside the dentinal tubules. No further LAC reduction was found after subsequent demineralization.ConclusionSDF and SDF+KI did not protect artificial enamel under acid attack even though Ag products were deposited in the porous enamel. However, SDF and SDF+KI shows protective properties against acid challenges and Ag products are deposited in carious dentin lesion without tubular structure randomly; and within dentinal tubules when these structures are retained.